Perturbation of a Two-Point Problem - Kengne, E. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We investigate the problem of the effect of integral terms in boundary conditions on the well-posedness of nonlocal boundary-value problems for partial differential equations.